Literature Riview: Potensi Antioksidan dan Antihiperglikemik In Vitro dan In Vivo dari Jamblang - Musfiroh, Eka Nurfarida; Herawati, Shintya Happy; Mahfud, Seftiani Su’aida; Fauziah, Syifa Salsabila Nur; Hidayah, Himyatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Antioxidants are one way to overcome the problem of free radicals. Diabetes is a group of metabolic diseases characterized by increased blood sugar levels and caused by impaired insulin secretion, impaired insulin action, or both. In vitro testing of glucose lowering activity was carried out using the Nelson-Somogyi method. Jamblang leaves are effective in normalizing glucose levels and controlling oxidative stress. This review aims to provide information regarding the potential of jamun as an antidiabetic drug so that it can be developed further. This research uses primary data sources. Collected through databases such as Google Scholar, several national journals can be searched as data sources. The results of this research indicate the presence of secondary metabolites such as alkaloids, flavonoids, saponins, terpenoids, tannins, steroids, phenolics, glycosides, cardiac glycosides, and resins in various plants, including bark, seeds, and leaves.